Basic Studies of Various 99mTc-Labelled Renal Agents and Clinical Application of 99mTc-Malate - Machida, T.; Miki, M.; Ueda, M.; Tanaka, A.; Ikeda, I. (Nuklearmedizin - NuclearMedicine, 1977)
Various renal imaging agents that were reported in the past and a new agent, 99mTc-malate as well as 99mTc-cystein acetazolamide complex were prepared using electrolysis and electrochemical methods. These were studied for their labelling efficiency. After animal experiments with selected 99mTc-com- pounds, 99mTc-rnalate proved to be sufficient for renal imaging with adequate concentration. 99mTcmalate differs from other renal imaging agents in the utilization of endogeneous metabolic product.The first half time of 99mTc-malate in humans is 17 minutes, on the average, and the urinary excretion rate of 99mTc-malate is 36±6.05% in 1 hour after intravenous administration, 44 ± 3.41% in 2 hours and 50 + 5.62% in 3 hours.In our 40 clinical experiences of 99m-Tc-rnalate, most cases demonstrated quite clear renal images in the serial scintiphotos except cases whose serum creatinines were over 4.5 mg/dl.